Pengaruh inklusivitas gender dalam pembelajaran terhadap motivasi belajar, kenyamanan gerak, dan hasil belajar senam lantai - Nelli Agustina; Fajar Ari Widiyatmoko; Pandu Kresnapati (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
Differences in learning motivation, movement comfort, and learning outcomes of floor gymnastics between male and female students are challenges in physical education activities. This phenomenon indicates that gender factors influence students' psychomotor and psychological readiness, so a learning model that can create equal interactions is needed. This study aims to analyze the impact of gender-inclusive learning on learning motivation, movement comfort, and learning outcomes of grade IX students at SMP Institut Indonesia Semarang using a quasi-experimental non-equivalent control group design consisting of a control group with non-inclusive learning and an experimental group with gender-inclusive learning. The intervention was implemented over three meetings, with 2 treatments given to each group. This study involved 48 students consisting of 23 students in the experimental class and 25 students in the control class. comes from one school so that the generalization of the findings is limited. The research instruments were the ARCS model learning motivation questionnaire, the PACES-18 movement comfort questionnaire, and the floor gymnastics learning outcome test. Significant results indicated an increase in the experimental class group with learning motivation scores (70.22 → 83.78), movement comfort (12.39 → 17.39), and learning outcomes (12.65 → 17.91). Statistical tests showed that the independent t-test analysis of the learning motivation posttest variable showed a significance value of 0.000 (p < 0.05). Meanwhile, the Mann–Whitney U test for movement comfort posttest showed a significance of 0.000 (p < 0.05). Meanwhile, the learning outcomes posttest showed a significance of 0.000 (p < 0.05). These findings confirm that gender-inclusive learning provides significant improvements in all three variables, thus recommending it as an effective learning strategy for floor gymnastics.